Biogenic silver nanoparticles improve bioactive compounds in medicinal plant Juniperus procera in vitro - Salih, Abdalrhaman M.; Al-Qurainy, Fahad; Khan, Salim; Nadeem, Mohammad; Tarroum, Mohamed; Shaikhaldein, Hassan O. (Frontiers in Plant Science, 2022)
Bioactive compounds of medicinal plants present as natural ingredients provide health benefits beyond the basic nutritional value of these products. However, the availability of bioactive compounds in the current natural source is limited. Hence, the induction of bioactive compounds production from medicinal plants through nanoparticles might be played a vital role in industrially important medicinal compounds. Therefore, this study aimed to synthesize silver nanoparticles (AgNPs) biologically and to investigate their effect on phytochemical compounds production from the callus of medicinal plant (Juniperus procera). Silver nanoparticles were synthesized biologically using aqueous leaves extract of Phoneix dactylifera, which acted as stabilizing and reducing, and capping agent and silver nitrate solution. The formation of AgNPs has been confirmed through different analytical techniques (UV, FTIR, DLS, and TEM). The impact of different concentrations (0.0, 5, 20, and 50 mg/L) of AgNPs on enzymatic and non-enzymatic antioxidants of callus of Juniperus procera was investigated. The obtained results showed a significant effect of AgNPs on biomass accumulation, and non-enzymatic antioxidants (phenol, tannin, and flavonoid contents). Also, total protein content and SOD activity were increased in response to AgNPs. Further, molecules like gallic acid, tannic acid, coumarin, hesperidin, rutin, quercetin, and ferruginol were chromatographically separated and quantified using HPLC with authentic standards. These compounds were increased significantly in response to AgNPs treatments. We concluded that silver nanoparticles can be a promising elicitor for improving the production of phytochemical compounds in medicinal plants through the induction of these compounds. This work can serve as a good model for improving the antioxidant system of medicinal plants in vitro which can be increased bioactive compound production. Further, the molecular investigation should be done for a better understanding of the metabolic mechanism that leads to the scaling up of bioactive compounds production.